Identifying money and inflation expectation shocks on real oil prices - Szilárd Benk; Max Gillman (Bank of Finland, 2023)
The paper adds money supply and inflation expectations shocks to a well-known three-variable structural model that identifies oil price shocks through fundamentals affecting the oil market. Impulse responses show the significance of our two additional monetary shocks in impacting real oil prices. By subtracting from the money supply the temporary Federal Reserve swaps that were used to increase liquidity during the 2008 and 2020 bank crises, shocks upwards in both the adjusted M1 money supply and to inflation expectations significantly increase real oil prices; with the unadjusted M1 aggregate there is no signiÖcant effect of money supply shocks on real oil prices. Decomposition of historical oil price shocks shows a significant role played by inflation expectations and the money supply shocks during major oil shock episodes. These shocks partially replace roles previously attributed to the precautionary oil demand shock and the aggregate demand shock during the three major oil shock periods of the 1970s-1980s, post-2008 and during the 2020-2021 pandemic. The results show that both real oil price shocks and expected inflation shocks cause real GDP to fall.
Keywords: Q41; Q43; E31; E52; 330; Real Oil Price Shocks; SVAR; Money Supply; Inflation Expectations